The Effect of Community Health Center on Visual Acetic Acid Uptake in Pati, Central Java - Retno Wulan; Pawito Pawito; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Cervical cancer is included in the category of malignant tumors that arise in the cervix of women. The incidence of cervical cancer is high due to lack of awareness to make efforts to examine early detection of cervical cancer by using the visual inspection acetic acid (VIA) method. The purpose of this study was to analyze the effect of community health center on the use of VIA.Subjects dan Method: This was an analytic observational study with a cross sectional design. was The study was conducted at 29 community health centers in Pati, Central Java. A sample of 232 women was selected by simple random sampling. The dependent variable was VIA uptake. The independent variable were perceived susceptibility, perceived seriousness, cues to action, perceived threat, perceived benefit, perceived barrier, self-efficacy, economic status, and social capital. The data were collected by questionnaire and analyzed by a multilevel multiple logistic regression run on Stata 13.Result: Community health center had a contextual effect on VIA uptake with intra-class correlation (ICC)= 16.91%. VIA uptake increased with high perceived susceptibility (b= 3.21; 95% CI= 0.22 to 6.19; p = 0.035), high perceived seriousness (b= 4.68; 95% CI= 1.06 to 8.29; p= 0.011), high perceived threat (b= 4.03; 95% CI= 0.61 to 7.45; p= 0.021), high perceived barrier (b= 2.48; 95% CI= 0.06 to 4.91; p= 0.044), high perceived benefit (b= 2.50; 95% CI= 0.10 to 4.91; p= 0.041), and high economic status (b= 11.22; 95% CI= 3.64 to 18.81; p= 0.004). VIA uptake decreased with low cues to action (b= -0.92; 95% CI= -3.08 to 1.24; p= 0.405), low self-efficacy (b= -0.32; 95% CI= -2.45 to 1.80; p= 0.765), and low social capital (b= 0.79; 95% CI= 3.64 to 18.81; p= 0.562).Conclusion: Community health center had a contextual effect on VIA uptake. VIA uptake increases with high perceived susceptibility, high perceived seriousness, high perceived threat, high perceived barrier, high perceived benefit, and high economic status. VIA uptake decreases with low cues to action, low self-efficacy, and low social capital.Keywords: Community Community health center, Acetic Acid Visual Inspection.Correspondence: Retno Wulan. Masters Program of Public Health, Universitas Sebelas Maret, JL. Ir.Sutami 36A, Surakarta, Central Jawa, Indonesia. E-mail: wuland.cimmutzz12@gmail.com. Mobile: 085740969271.Journal of Health Promotion and Behavior (2019), 4(3): 189-197https://doi.org/10.26911/thejhpb.2019.04.03.04